The Effect Of Stevia Sugar On The Sensory And Antioxidant Properties Of Functional Drink From Telang Flower (Clitoria Ternatea L.) - nizori, addion (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
Butterfly pea flowers can be used as a functional drink because they contain phytochemical compounds such as tannins, saponins, triterpenoids, polyphenols, phenols, flavonoids, glycosides, alkaloids and steroids. The addition of stevia sugar provides a sweet taste to the butterfly pea flower functional drink, making it more appealing to consumers. Stevia sugar is a low-calorie and low-sugar sweetener. The purpose of this study was to determine the effect of stevia sugar concentration on the characteristics of the telang flower functional drink and to determine the best stevia sugar concentration in the butterfly pea flowersfunctional drink. This study used a completely randomized design (CRD) consisting of 5 levels of treatment, namely ( 0%, 0.1%, 0.2%, 0.3% and 0.4%) stevia sugar and then repeated 4 times to obtain 20 unitstest. The results showed that the concentration of stevia sugar had a significant effect on total soluble solids (TPT), taste hedonic quality, and overall acceptance (sensory) but had no significant effect on color degree, acidity (pH), % inhibition, and color. Functional drinks with the addition of 0.3% stevia sugar gave the best results with the characteristic description of pure blue color, pH 5.02, total soluble solids 1.03 Brix, antioxidant 71.61% inhibition, overall acceptance 3.56 (slightly like – like)